Socioeconomic inequalities in the use of dental services in Brazil: an analysis of the 2019 National Health Survey - Maria Laura Braccini Fagundes; Lucelen Fontoura Bastos; Orlando Luiz do Amaral Júnior; Gabriele Rissotto Menegazzo; Amanda Ramos da Cunha; Caroline Stein; Lucas Guimarães Abreu; Fernando Neves Hugo; Jessye Melgarejo do Amaral Giordani; Deborah Carvalho Malta; Betine Pinto Moehlecke Iser
ABSTRACT: Objective: To describe the prevalence of use of dental services in Brazil according to states and the Federal District and its relationship with socioeconomic variables and types of services, based on the 2019 National Health Survey. Methods: This is a cross-sectional population-based study using data from the 2019 National Health Survey, which included 88,531 participants aged 18 or older. We assessed variables related to the use of dental health services according to sociodemographic and behavioral characteristics through multivariate analysis, using a Poisson regression model with robust variance. Results: The use of dental services in the year prior to the interview was higher among adults (53.2%, confidence interval - 95%CI 52.5-53.9) than older adults (34.3%, 95%CI 33.2-34.4). The multivariate analysis revealed that the use of dental services was greater in people with better schooling (prevalence ratio - PR=2.02, 95%CI 1.87-2.18) and higher income (PR=1.54, 95%CI 1.45-1.64). States from the Southeast, Midwest, and South regions presented the highest percentages of individuals who visited a dentist in the previous year - between 49.0 and 57.6% of the population. Conclusion: Inequalities were found in the use of dental health services among the adult and older adult population, with regional differences; the use was higher among women, younger individuals, those with better schooling, higher income, healthier behaviors, better self-perceived oral health status, and who paid for their last dental treatment.